Estimation of stature and sex by foot length measurements using linear regression and discriminant function analysis, respectively: A study in central india population - Rekha Lalwani; Himank Gupta; Sunita A Athavale; Sheetal Kotgirwar (Wolters Kluwer Medknow Publications, 2019)
Background and Aim In forensic investigations establishing the identity of a person is a vital step. Stature and sex are important attributes of personal identity. In cases of mass disasters, generally isolated body parts and extremities are recovered as remains and are utilized to ascertain identity of an individual with personal attributes like gender, stature. The present study was conducted to ascertain if the foot length can be reliably used in estimation of stature and gender, and to establish population-specific regression equation and discriminant function analysis in population of Central India. Methods One hundred subjects (50 males and 50 females) between the age group of 20 and 40 years, who are residents of Central India for two generations, were studied. Foot length, of both right and left sides, was recorded for each individual and stature was measured with the help of a stadiometer. Data were subjected to statistical analysis. Results Statistical analysis of the data of the study population showed statistically highly significant differences (p < 0.001) between males and females. Statistically highly significant positive correlation was observed between stature and foot length in males and females. Linear regression equations for stature estimation were derived separately for males and females. The discriminant function analysis, utilizing foot length correctly, classified 78 to 85.1% of cases for respective gender. Conclusion The statistically significant positive correlation between the foot length and stature and accuracy of sex classification by discriminant function analysis indicate the reliability of foot length in predicting stature and gender of an individual.